2018
DOI: 10.1017/s1368980018002896
|View full text |Cite|
|
Sign up to set email alerts
|

The Third French Individual and National Food Consumption (INCA3) Survey 2014–2015: method, design and participation rate in the framework of a European harmonization process

Abstract: ObjectiveAssessing dietary exposure or nutrient intakes requires detailed dietary data. These data are collected in France by the cross-sectional Individual and National Studies on Food Consumption (INCA). In 2014–2015, the third survey (INCA3) was launched in the framework of the European harmonization process which introduced major methodological changes. The present paper describes the design of the INCA3 survey, its participation rate and the quality of its dietary data, and discusses the lessons learned f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 32 publications
(37 reference statements)
0
47
0
Order By: Relevance
“…However, the French INCA 3 consumption study reported in 2017 the mean omega-3 consumption as follows: 1 g/day of ALA instead of the 2.2 recommended, and 286 mg/day of EPA + DHA instead of 500 recommended. Therefore, only 15% of the French population meet DHA intake recommendation, only 8% for EPA and only 1.6% for ALA [ 9 , 32 ]. Breast milk composition is also a good biomarker for PUFAs intake levels.…”
Section: Omega-3 Pufa Dietary Intake Levels Are Largely Below the Recmentioning
confidence: 99%
“…However, the French INCA 3 consumption study reported in 2017 the mean omega-3 consumption as follows: 1 g/day of ALA instead of the 2.2 recommended, and 286 mg/day of EPA + DHA instead of 500 recommended. Therefore, only 15% of the French population meet DHA intake recommendation, only 8% for EPA and only 1.6% for ALA [ 9 , 32 ]. Breast milk composition is also a good biomarker for PUFAs intake levels.…”
Section: Omega-3 Pufa Dietary Intake Levels Are Largely Below the Recmentioning
confidence: 99%
“…In the European Union, goats' milk production accounted for only 1.4% of total milk production [37]. In the French nutritional survey, previously mentioned, 0.4% of people reported drinking goats' milk (2; personal communication, SpF). Fifteen per cent of people reported eating any type of goats' milk cheese, and 3% reported eating raw goats' milk cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Raw milk cheeses are popular in France accounting for 15% of all mature French cheeses, 75% of protected designation of origin (PDO) and protected geographical indication (PGI) cheeses, and the majority of other artisanal cheeses [1]. In the most recent national nutritional survey, 32% of people reported having eaten a raw milk cheese in at least one of three non-consecutive days in the previous 3 weeks [2]. Collaterally, raw milk cheeses have been the vehicle of 16 major Salmonella foodborne outbreaks (FBO) in France between 2008 and 2018, representing a third of Salmonella outbreaks with an identified source [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Third French Individual and National Food Consumption (INCA3) Survey 2014-2015 was a cross-sectional study carried out between February 2014 and September 2015 among a representative sample of individuals living in mainland France. The objectives, design and methodology have been described before (26) . This study was conducted according to the guidelines laid down in the Declaration of Helsinki, and all procedures involving human subjects/patients were approved by the (CCTIRS, no.…”
Section: Studymentioning
confidence: 99%